2011
DOI: 10.2341/10-253-l
|View full text |Cite
|
Sign up to set email alerts
|

Microleakage and Marginal Gap of Adhesive Cements for Noble Alloy Full Cast Crowns

Abstract: Recently introduced self-adhesive resin cements showed an improved sealing ability for noble alloy full cast crowns compared with a resin-modified glass ionomer or dual-cured resin cement. SUMMARYVery limited comparative information about the microleakage in noble alloy full cast crowns luted with different types of adhesive resin cements is available. The purpose of this study was to evaluate the microleakage and marginal gap of two self-adhesive resin cements with that of other types of adhesive luting cemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
35
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 22 publications
(37 reference statements)
7
35
1
Order By: Relevance
“…[4][5][6] However, little information is available about these chemical reactions, and the durability of this bonding requires further investigation, since clinicians have switched from conventional resin cement to these new self-adhesive resin cements. [7][8][9] Declaration of Interests: The authors certify that they have no commercial or associative interest that represents a conflict of interest in connection with the manuscript.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] However, little information is available about these chemical reactions, and the durability of this bonding requires further investigation, since clinicians have switched from conventional resin cement to these new self-adhesive resin cements. [7][8][9] Declaration of Interests: The authors certify that they have no commercial or associative interest that represents a conflict of interest in connection with the manuscript.…”
Section: Introductionmentioning
confidence: 99%
“…[29] The other vision for authors on adhesive bonding is selfadhesive resin luting cements which does not require detailed technical steps. Hooshmand et al [41] reported self-adhesive resin luting cements have better marginal microleakage results than conventional resin luting cements. Amaral et al [21] compared different adhesive systems used with glass fiber posts in root canals on the pullout strength.…”
Section: Discussionmentioning
confidence: 98%
“…For the cementation process of ZP, 1.4-mm ZP (Cosmopost, Ivoclar Vivadent, Amherst, NY) which was made from zirconium oxide ceramic and consisted of HFO 2 , Y 2 O 3 , and Al 2 O 3 were selected. Root canals were [33,34] and into root canals, and the posts were placed in the root canals. Smartcem 2 (Dentsply DeTrey, GmbH, Konstanz, Germany) is a self-adhesive resin cement which does not require any application step.…”
Section: Methodsmentioning
confidence: 99%
“…In a study of Kassem et al [34] Panavia F 2.0 showed less microleakage results than Rely X Unicem. In contrast to these studies, Hooshmand et al [36] evaluated microleakage values of noble alloy full cast crowns which were cemented with variable luting cements and they reported that Panavia F 2.0 showed higher microleakage results.…”
mentioning
confidence: 91%
“…The root canals in group of PAN/ED were conditioned with Panavia 2.0 ED Primer II (Kuraray Co Ltd, Osaka, Japan) with microbrushes (White, 1.0 mm, Micro-brush Disposable Micro-Applicator; Microbrush, Grafton, Wis.) for 60 s [30,33,34]. Panavia F 2.0 resin cement was applied on the post surfaces[35,36] and into root canals, the posts were placed in the root canals. For the RU group, Rely X Unicem self adhesive resin cement directly applied to the post surfaces and placed into the root canals.…”
mentioning
confidence: 99%